EWOLUTION: Design of a registry to evaluate real‐world clinical outcomes in patients with AF and high stroke risk‐treated with the WATCHMAN left atrial appendage closure technology. Issue 3 (31st December 2015) - Boersma, Lucas V.A.; Schmidt, Boris; Betts, Tim R.; Sievert, Horst; Tamburino, Corrado; Teiger, Emmanuel; Stein, Kenneth M.; Bergmann, Martin W.
Abstract : Background: Atrial fibrillation (AF) is the most common sustained cardiac arrhythmia and the rate of ischemic stroke attributed to non‐valvular AF is estimated at 5% per year. Several multi‐center studies established left atrial appendage closure as a safe and effective alternative to oral anticoagulation, but there is a need for additional real world data. Methods: The purpose of this observational, prospective, single‐arm, multicenter clinical study is to compile real‐world clinical outcome data for WATCHMAN™ LAA (left atrial appendage) Closure Technology. One thousand subjects at up to 70 institutions in Europe, the Middle East, and Russia will be enrolled. Patients will be followed for 2 years after WATCHMAN implantation, according to standard medical practice. Primary endpoints include procedural and long‐term data including stroke/embolism, bleeding, and death. This article presents the background of the LAAC device and describes the design of the study. Results: Results for peri‐procedural analyses are expected toward the end of 2015; long‐term follow‐up data are expected in the latter half of 2017. Conclusion: The EWOLUTION study will formally expand knowledge of LAA closure into a broader real world setting. © 2015 Wiley Periodicals, Inc.